STRATEGI PROMOSI PERPUSTAKAAN IAIS SAMBAS MENARIK KUNJUNG PEMUSTAKA - Azwar Azwar (CV. ADIBA AISHA AMIRA, 2023)
Library promotion aims to attract visitors to the library. The IAIS Sambas Library is a university library that provides sources of information to students. This study looks at the extent to which promotion is carried out by the IAIS Sambas library. The method used is a qualitative method with a case study approach. Data collection techniques are interviews, observations, and literature studies. The data analysis technique used is data reduction, data presentation, and drawing conclusions. Based on the results of data processing, it can be concluded that the IAIS Sambas library in promotion planning conducts user target analysis, library SWOT analysis, and determines the purpose of library promotion to determine which promotional media will be used. The promotion of the IAIS Sambas library uses individual sales, use of Facebook social media, blogs and word of mouth, and direct sales (whatsapp and email). The obstacle faced by the Pustakalana library in carrying out promotions was the lack of human and financial resources, so that the implementation of several activities was hampered.